Climate Vulnerability Assessments : An Assessment of Climate Change Vulnerability, Risk, and Adaptation in Albania's Energy Sector - World Bank (Washington, DC, 2014)
Many countries are increasingly vulnerable to destructive weather events, floods, droughts, windstorms, or other parameters. The vulnerability is driven in part by recent extremes in climate variability but also by countries' sensitivity to events exacerbated by past practices, socioeconomic conditions, or legacy issues. The degree to which vulnerability to weather affects the countries' economies is driven by their coping or adaptive capacities. This overview showcases a pilot vulnerability, risk, and adaptation assessment undertaken for Albania's energy sector to raise awareness and initiate dialogue on energy sector adaptation. This pilot assessment demonstrates an approach that can be used to help countries and energy sector stakeholders develop policies and projects that are robust in the face of climatic uncertainties, and assist them in managing existing energy concerns as the climate changes. It identifies key direct risks to energy supply and demand and options for adaptation to establish where to focus subsequent in-depth analyses. It also identifies additional research needed to better understand the implications of extreme climatic events for the energy sector as well as potential indirect impacts, such as possible adaptation actions in the agriculture sector that may affect energy supply.